Moonbird : a year on the wind with the great survivor B95 - Hoose, Phillip (New York : Scholastic Inc., 2012)
Moonbird: a year on the wind with the great survivor B95 I always know that a book by Phil Hoose will take a complex subject and make it understandable, while maintaining a sense of awe and wonder, and this book is no exception. This amazing bird, flying across hemispheres, faces challenges of endurance, climate, geography, politics, and more, which are all explained with the perfect balance of science and storytelling. I highly recommend it. Moonbird. In the next few months, from March to June, B95 and his flock mate will fly from the bottom of the world to the top from the land of penguins to polar bear country.
Moonbird: un año en el viento con el gran sobreviviente B95 Siempre sé que un libro de Phil Hoose tomará un tema complejo y lo hará comprensible, mientras mantiene un sentido de asombro y admiración, y este libro no es una excepción. Esta asombrosa ave, que vuela a través de hemisferios, enfrenta desafíos de resistencia, clima, geografía, política y más, que se explican con el equilibrio perfecto de la ciencia y la narración. Lo recomiendo altamente. Pájaro lunar En los próximos meses, de marzo a junio, B95 y su compañera de vuelo volarán desde el fondo del mundo a la cima desde la tierra de los pingüinos hasta el país del oso polar.
CONTENTS CHAPTER ONE: SUPERBIRD CHAPTER TWO: CLIVE MINTON CHAPTER THREE: SHOWDOWN AT TRAPPING CHAPTER FOUR: TWINKLING AND TRAPPING CHAPTER FIVE: THE ARCTIC BREEDING
Includes alphabetic index
Incluye índice alfabético
Includes countries alphabetical index
Incluye índice alfabético de países
Keywords: BIRDS IN EXTINCTION; RARE BIRDS; AVES EN EXTINCIÓN; AVES RARAS